The Prevalence and Risk Factors of Low Back Pain Among Healthcare Workers in Asia - Ilmidin, Ilmidin; Situmeang, Irene Florensia; Sarasnita, Nina (The Indonesian Journal of Occupational Safety and Health, 2023)
Intorduction: Low Back Pain is a musculoskeletal disorder and not a disease. Among healthcare workers (HCw), this is the disorder they experience most often, and knowledge about the prevalence of of low back pain (LBP) and its risk factors among healthcare workers is important to determine appropriate training for them The purpose of this study was to identify the magnitude of low back pain (LBP) problems in HCw as well as to determine which risk factors are determinants. Method: This study used a systematic review via meta-analysis guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: Through a search of 13 articles from several countries in Asia, which analyzed 5753 respondents (1080 or 18.8% were males and 4673 or 81.2% were females), the average prevalence of LBP was 58.1%. This value was calculated without estimating the time span of its occurrence. If this range was calculated, of the 11 articles that calculated the lifetime incidence of LBP, the average was 60%. The risk factors were manual patient removal, heavy object lifting, sex, age, stress, type of work, workplace environment, and work duration. Conclusion: This study found a high prevalence, and there are still many risk factors for LBP that require special attention. Healthcare workers are advised to pay attention to ergonomics and working behavior, while hospital leaders are advised to conduct training on the risk factors of LBP.